Efficacy of tranexamic acid in improving visual clarity and operative time of arthroscopic rotator cuff repair: A systematic review and meta-analysis - Yushun Qian; Anqing Jiang; Jun Yan; Shouchun Zhang; Siqiang Zhu (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to examine if tranexamic acid (TXA) can assist in improving outcomes of arthroscopic rotator cu! repair (RCR).